Al-qur'an education park at el-hasan terban mosque, gondokusuman, yogyakarta city - Lilis Suryani; Barkah Lestari; Israa Al_barazanchi; Irfan Ahmad; Manvender Kaur Sarjit Singh (Peneliti Teknologi Teknik Indonesia, 2021)
El-Hasan Mosque is located in the denizen association Rukun Warga (RW) XII, Resonegaran habitation, Terban Village. Resonegaran is west of Purbonegaran Village, on the east side of Prof. Yohanes Street. Because of the mosque's renovation, The Quran education has temporarily stopped in the Quran education park located within the El-Hasan Mosque. Therefore, during the renovation’s vacuum period for Quran education, community service helped increase children's understanding of Islam and bring children closer to the Quran through recitation assistance, Iqro’ (reading), and memorizing the Juz’amma, short verses. The Qur'an Education Park activity program was implemented over the course of nine meetings with a total of twelve hours. The first six meetings were scheduled for six hours, one hour for each meeting, and the last three meetings for six hours, two hours for each meeting. The last three meetings were for memorization checks for the participants, which took longer times. The program was scheduled to take place every Wednesday and Friday of the week. The Quran Education Park Activity Program lasted for five meetings and eight hours.